An exploration of medical student attitudes towards disclosure of mental illness. Issue 1 (1st January 2020) - Fletcher, Ian; Castle, Michael; Scarpa, Aaron; Myers, Orrin; Lawrence, Elizabeth
ABSTRACT: Background : Medical students are reluctant to access mental health services, despite having high rates of anxiety and depression. This reluctance persists through residency and into practice. Physicians and trainees who are unwell deliver lower quality patient care, behave less professionally, communicate less effectively and are at an increased risk for burnout and suicide. Little is known about whether students would disclose a mental health diagnosis on a state board medical license application. Objectives : The objectives of this study were to determine whether University of New Mexico School of Medicine (UNM SOM) students would be willing to disclose a mental health diagnosis on a medical licensing application if prompted to do so, and, if not, to identify the reasons for their unwillingness to do so. Design : We electronically invited all UNM SOM students enrolled in the Classes of 2019, 2020, 2021, and 2022 to participate in a confidential RedCap survey about mental health diagnoses and treatment. Four e-mail invitations and reminders were sent to students over a one-month period. Results : Response rate was 50.1%. Thirty-six percent of all respondents considered themselves to have had a mental health condition prior to medical school, and 47% of all respondents perceived a decline in mental health during medical school. The majority of respondents who perceived they had a mental health diagnosis (51%) stated they would not disclose this information on a New Mexico Medical Board (NMMB) license application. Fear of stigmatization, fear of repercussions, and a belief that such disclosure was irrelevant were the top reasons for non-disclosure. Conclusion : Students who perceive themselves to have mental health diagnoses are unlikely to disclose their mental health status on state medical board licensing applications when asked to do so. Addressing barriers to disclosure of mental health diagnoses is necessary for building a healthier physician workforce.